Effect of Microsilica on Strength and Microstructure of the GGBS-based Cement composites. Issue 1 (November 2020) - Khan, M N; Singla, S; Garg, R; Garg, R
Abstract: Cement production requires substantial energy and significantly accounts for global carbon dioxide emissions. Thus, the consumption of ordinary portland cement (OPC) must be reduced through incorporation of auxiliary materials. Also, the mechanical strength and durability of structures, in the construction industry, need to be improved for economizing the maintenance cost and increasing the service life. This study explores the effect of partial substitution of cement by granulated blast furnace slag (GGBS), and microsilica (MS), the industrial by-products. This study focuses on the use of 10% GGBS and 0-16% MS as a substituent of cement at a water binder ratio of 0.42. The fresh properties were determined to study the effect of these substituents. The compressive strength of all the mixes was determined after 3, 7, 28, and 56 days of treatment. The results were correlated through microstructural analysis. The study revealed that the cement composites with an optimal substituent dosage of 10% GGBS and 12% MS can attain adequate compressive strength and can be used for practical applications.